Beyond risk: Prospective effects of GABA Receptor Subunit Alpha-2 (GABRA2) × Positive Peer Involvement on adolescent behavior. (17th June 2016) - Trucco, Elisa M.; Villafuerte, Sandra; Burmeister, Margit; Zucker, Robert A.
Abstract: Research on Gene × Environment interactions typically focuses on maladaptive contexts and outcomes. However, the same genetic factors may also impact susceptibility to positive social contexts, leading to adaptive behavior. This paper examines whether the GABA receptor subunit alpha-2 ( GABRA2 ) single nucleotide polymorphism rs279858 moderates the influence of positive peer affiliation on externalizing behavior and various forms of competence. Regions of significance were calculated to determine whether the form of the interaction supported differential susceptibility (increased sensitivity to both low and high positive peer affiliation) or vantage sensitivity (increased sensitivity to high positive peer affiliation). It was hypothesized that those carrying the homozygous minor allele (GG) would be more susceptible to peer effects. A sample ( n = 300) of primarily male (69.7%) and White (93.0%) adolescents from the Michigan Longitudinal Study was assessed from ages 12 to 17. There was evidence for prospective Gene × Environment interactions in three of the four models. At low levels of positive peer involvement, those with the GG genotype were rated as having fewer adaptive outcomes, while at high levels they were rated as having greater adaptive outcomes. This supports differential susceptibility. Conceptualizing GABRA2 variants as purely risk factors may be inaccurate. Genetic differences in susceptibility to adaptive environmental exposures warrants further investigation.